Lead Titanate-Based Nanocomposite: Fabrication, Characterization and Application and Energy Conversion Evaluation - Sakamoto, Walter Katsumi; Jr, Gilberto de Campos Fuzari; Zaghete, Maria Aparecida; Freitas, Ricardo Luiz Barros de (IntechOpen, 2011)
None